Hägnutnyttjande och besökarpåverkan på Humboldtpingviner (Spheniscus humboldti) - Källström, Victoria (2020)
The aim of this study was to examine enclosure utilization and visitor effect on the Humboldt penguin at Slottsskogen located in Gothenburg, Sweden in order to use the results to possibly improve welfare for both this flock and other flocks in captivity. The Humboldt penguin is a threatened species and therefor it is of the most importance to work towards conservation and a way to do this is by keeping and letting them reproduce in zoos. There are different ways to look at visitor effects and research on different species in varying surroundings has shown contrasting results. Positive, negative and neutral effects have been seen and not much research has been conducted in this area regarding the Humboldt penguin. The method used was scan sampling with intervals of five minutes for two hours, three sessions a day, for twelve days. The enclosure was divided into seven different zones with varying environments. The flock consisted of 32 individuals in varying ages raised in the enclosure. The results indicate that this flock does not seem to be negatively affected by visitor numbers or intensity when it comes to enclosure utilization as the whole enclosure is used by the penguins. They also spent a lot of time in the water swimming (18 %) which can be argued to be an important natural behaviour for the Humboldt penguin. The results regarding visitor effects were difficult to interpret as it was not clear if the penguins were not affected by visitors, if visitors actually attracted the penguins or if the visitors were attracted to the enclosure when high levels of activity was shown. More research is needed to conclude if this only applies to this particular group or if Humboldt penguins in zoos are not affected by visitors in general.